TELAAH SOSIOKULTURAL NASKAH DRAMA DEATH OF A SALESMAN KARYA ARTHUR MILLER - Bustami Subhan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2006)
There are at least three main reasons for the writer to conduct a research on the play Death of A Salesman by Arthur Miller. First, the play Death of A Salesman was Arthur Miller’s masterpiece that brought him to the winner of Pulitzer Prize, the New York Drama Critics’ Circle Award, the Antoinette Award, the Theatre Club Award, and the Front Page Award. The play presents a male protagonist who changed his profession from a carpenter to a salesman—this phenomenon is interesting since the setting of the play corresponds to the period of business growth in the United States of America. Second, the play contains many aspects: economic, social, cultural, psychological and moral. Third, the play contains special background and modern contexts that can be inferred into individual experience or consciousness especially for a father who wants to create a business and a happy family in a turbulent world. This writing is aimed at portraying the economic and socio-cultural aspects as reflected in the play, and revealing the moral values that can be taken from the play Death of a Salesman by Arthur Miller.